2023
DOI: 10.1093/pnasnexus/pgad229
|View full text |Cite
|
Sign up to set email alerts
|

SUB1A-1 anchors a regulatory cascade for epigenetic and transcriptional controls of submergence tolerance in rice

Abstract: Most rice (Oryza sativa) cultivars cannot survive under prolonged submergence. However, some O. sativa ssp. indica cultivars, such as FR13A, are highly tolerant owing to the SUBMERGENCE 1A-1 (SUB1A-1) allele, which encodes a Group VII ethylene-responsive factor (ERFVII) protein; other submergence-intolerant cultivars contain a SUB1A-2 allele. The two alleles differ only by a single substitution at the 186th amino acid position from serine in SUB1A-1 to proline in SUB1A-2 resulting in only SUB1A-1 being able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Populations carrying SUB1A have two alleles, SUB1A-1 and SUB1A-2. The only difference between the two alleles is the presence of a proline residue at position 186 in SUB1A-2, instead of a serine residue in SUB1A-1 [15,17,19,58]. SUB1A-1 is specifically identified in submergence-tolerant cultivars, such as FR13A, and it can be strongly induced upon submergence to exert a determinant role in submergence stress responses, whereas the SUB1A-2 allele, which is only found in submergence-sensitive cultivars, such as IR29, is poorly induced during submergence [15,58].…”
Section: Sub1a Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Populations carrying SUB1A have two alleles, SUB1A-1 and SUB1A-2. The only difference between the two alleles is the presence of a proline residue at position 186 in SUB1A-2, instead of a serine residue in SUB1A-1 [15,17,19,58]. SUB1A-1 is specifically identified in submergence-tolerant cultivars, such as FR13A, and it can be strongly induced upon submergence to exert a determinant role in submergence stress responses, whereas the SUB1A-2 allele, which is only found in submergence-sensitive cultivars, such as IR29, is poorly induced during submergence [15,58].…”
Section: Sub1a Pathwaymentioning
confidence: 99%
“…SUB1A-1 also activates the transcription of other Group VII ERF transcription factors, such as ERF66 and ERF67, and enhances submergence tolerance by regulating various hypoxia-responsive genes [60]. Recently, one report showed that SUB1A-1 can interact with ADA2b (ALTER-ATION/DEFICIENCY IN AC-TIVATION 2) of the ADA2b-GCN5 (GENERAL CONTROL NON-REPRESSIBLE 5) acetyltransferase complex and recruits this complex to modify the chromatin structure of the ERF66/ERF67 promoter region and activate gene expression, which in turn enhances rice submergence tolerance [58]. In addition, the expression of DWARF1 (DWF1) and DWARF4 (DWF4), two key genes involved in the biosynthesis of brassinosteroids (BRs), is significantly higher in M202-Sub1 (tolerant variety) than in M202 (intolerant variety) during submergence, suggesting that SUB1A-1 can activate BR signaling.…”
Section: Sub1a Pathwaymentioning
confidence: 99%